EVALUATION OF BIOFILM FORMING ABILITY OF THE MULTIDRUG RESISTANT PSEUDOMONAS AERUGINOSA - S. NAGAVENI; H. RAJESHWARI; AJAY KUMAR OLI; S. A. PATIL; R. KELMANI CHANDRAKANTH (The Bioscan, 2010)
Biofilm formations of 25 clinical isolates of Pseudomonas aeruginosa were screened by Tissue Culture Plate (TCP), Tube Method (TM) and Congo Red Agar (CRA) method. The susceptibility tests showed that majority of the organisms were multidrug resistant with 86%. Based on the biofilm-positive phenotype, the strains were classified as high, moderate and weak or no biofilm was detected. Of the 12 isolates screened, 3 isolates were high biofilm producers, moderate and weak production was seen in 3 isolates for each type. However, TM correlated TCP but was difficult to detect biofilm negative isolates. Screening by CRA method was not remarkable. Hence, it was found that TCP method is highly sensitive method for detection of biofilm producing P. aeruginosa.